Media Audio Visual Berbahasa Arab terhadap Penguasaan Mufradat (Kosakata) - M, Fany Fadillah; Susiawati, Susiawati; Saleh, Nurming (Academic : Journal of Social and Educational Studies, 2025)
Abstract. This study aims to improve the mastery of Arabic vocabulary in class VIII students of SMP IT Wahdah Islamiyah Makassar using audio-visual media. This type of research uses a quantitative approach with a Quasi Experimental Design research method in the form of Nonequivalent Control Group Design. The population in this study were all VIII grade students totalling 93 people, while the samples in this study were VIII B2 students with 31 students as the experimental class and VIII B1 students with 31 students as the control class. The results showed that: Arabic language learning through the use of audio-visual media in Arabic can improve the mastery of mufradat of class VIII students of SMP IT Wahdah Islamiyah Makassar. The increase is indicated by the average value (mean) obtained from the initial test (pre-test) which is 41.03 and the average value (mean) obtained from the final test (post-test) which is 74.84. The results of data analysis of hypothesis testing at a significant level of 0.05 obtained a value (2-tailed) of 0.001 <0.05. It can be concluded that the use of audio-visual media in Arabic is effective on the mastery of vocabulary of class VIII students of SMP IT Wahdah Islamiyah Makassar.Keywords: learning media, audio visual, mastery of mufradat (Arabic vocabulary)